Integrating technologies for the sustainable control of gastrointestinal parasites in sheep : The Argentinean case - Poli, Mario Andres (2023)
Gastrointestinal nematode infections in sheep are a major concern among breeders due to the economic losses they cause in terms of a reduction in both productivity and viability of animals. The situation worsens in face of the emergence of anthelmintic-resistant parasites. In this context, breeding and management practices aimed at an integrated control of parasites, such as raising parasiteresistant sheep, are required. This study focused on the genetic variation underlying parasite resistance in sheep, for potential use in breeding programmes. An artificial challenge with infectious H. contortus L3 was carried out in the northeast region of Argentina for more than 10 years in 1 072 Corriedale lambs with an average age of 5.6 months. Body weight, faecal egg count, packed cell volume, and FAMACHA© score were recorded at different time points post-challenge and their heritability and phenotypic and genetic correlations were estimated. Animals were genotyped on 173 single nucleotide polymorphisms belonging to 77 candidate genes for immune response. The results indicate that there is sufficient genetic variability for the four traits studied, which presented moderate heritabilities (in the range 0.29 to 0.44) and increased along the challenge period, with the exception of the hematocrit, which decreased. Association analyses identified seven markers associated with estimated breeding values for faecal egg count, located in genes involved in different stages of the pathogen-host interaction process. The information obtained supports the potential of markerassisted breeding schemes to enable profitable and sustainable sheep production.